The field oriented control of a permanent magnet synchrounous motor (PMSM) by using fuzzy logic - Iderus, Samat (2014)
This project presents the comprehensive performance analysis on the principle of operation, design considerations and control algorithms of the field oriented control (FOC) for a permanent magnet synchronous motor (PMSM) drive system of Fuzzy Logic Controller (FLC) and proportional-integral PI for speed control in closed loop operation. To perform speed control of typical PMSM drives, PI controllers and FOC method are classically used. PI Controller controller suffers from the drawback that for its proper performance, the limits of the controller gains and the rate at which they would change have to be appropriately chosen. Fuzzy based gain scheduling of PI controller has been proposed in which uses in order to overcome the PI speed controller problem. The simulation results show that the proposed FLC speed controller produce significant improvement control performance compare to the PI controller. FLC speed controller produced a better performance than PI speed controller where the overshoot is totally removed and the settling time faster than PI speed controller in achieving desired output speed. The fuzzy algorithm is based on human intuition and experience and can be regarded as a set of heuristic decision rules. It is possible to obtain very good performance in the presence of varying load conditions changes of mechanical parameters and inaccuracy in the process modelling. Research and application of fuzzy logic are developing very rapidly, with promising impacts on electric drives and power electronics in future. Keywords: FOC, PMSM, FLC, PI and for Speed Control.